Report of Director to Trustee N. Ellery, State Engineer, April 22, 1910 - H. B. Waters::::::author::: (1910)
A report prepared by H.B. Waters and sent by the Cal Poly Director Leroy Burns Smith to the California State Engineer. The report reviews the California Polytechnic School's proposed and current water systems. The school wanted a system to develop a water site at the northwest corner of the school farm near the Southern Pacific right of way and Brizzolara Creek so that the students could irrigate the field north of the main buildings and to apply the water to the lawns and plantings adjacent to the main group of buildings. The present pumping plant was in Brizzolara Canyon at the northeast corner of the farm, which provided an abundant high pressure supply for domestic use at the campus buildings and for the lawn around dormitory 2 (Deuel Hall). Report addresses drilling and testing of wells, a pumping plant, laying irrigation pipe, and water tanks capacity. H. B. Waters was the Vice Director of the School as well as a professor of Physics and Electricity in the mechanics department.